2009
DOI: 10.1091/mbc.e08-03-0302
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein and Its A30P Mutant Affect Actin Cytoskeletal Structure and Dynamics

Abstract: The function of ␣-synuclein, a soluble protein abundant in the brain and concentrated at presynaptic terminals, is still undefined. Yet, ␣-synuclein overexpression and the expression of its A30P mutant are associated with familial Parkinson's disease. Working in cell-free conditions, in two cell lines as well as in primary neurons we demonstrate that ␣-synuclein and its A30P mutant have different effects on actin polymerization. Wild-type ␣-synuclein binds actin, slows down its polymerization and accelerates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 53 publications
7
96
0
Order By: Relevance
“…27 We previously demonstrated that actin is a target for intracellular Syn, and that wt and A30P-mutated Syn differentially modulate actin dynamics. 13 Here, we provide evidences that the extracellular accumulation of either wt or A30P Syn correlates with an unbalance of actin turnover, resulting in microfilament stabilization. Extracellular Syns, delivered either as purified monomeric proteins in unfolded conformation or with the medium of overexpressing neurons, induced the formation of large lamellipodia-like actin protrusions along the neurites and at their tips.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…27 We previously demonstrated that actin is a target for intracellular Syn, and that wt and A30P-mutated Syn differentially modulate actin dynamics. 13 Here, we provide evidences that the extracellular accumulation of either wt or A30P Syn correlates with an unbalance of actin turnover, resulting in microfilament stabilization. Extracellular Syns, delivered either as purified monomeric proteins in unfolded conformation or with the medium of overexpressing neurons, induced the formation of large lamellipodia-like actin protrusions along the neurites and at their tips.…”
Section: Discussionmentioning
confidence: 57%
“…We previously demonstrated that Syn can physiologically control actin turnover, activity that is altered in the Syn A30P mutant. 13 As Syn is released from neurons, we wondered whether high levels of extracellular Syn could affect actin dynamics in a similar way. The morphology of the actin cytoskeleton was monitored in young hippocampal neurons after incubation for 1 h with 1 mM purified human recombinant wt or A30P Syn.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the animal experiments was shown that α-synuclein participates in the trafficking of synaptic vesicles and in the regulation of the exocytic [31] and fusion processes [32]. One of its roles in synaptic activity is performed by interaction with actin in order to regulate the synaptic vesicle mobilization [33] demonstrated by inhibition of actin polymerization and cytoskeletal disruption caused by the mutant α-synuclein [34]. α-synuclein is involved in the SNARE-complex assembly with possible implications during aging [35].…”
Section: Medical and Clinical Reviews Issn 2471-299xmentioning
confidence: 99%